Hubungan Self-Efficacy dan Emotional Intelligence dengan Stress Akademik Mahasiswa Sarjana Keperawatan di STIKES Sukabumi - Novianty, Lia; Utami , Rima Novianti; Ahmad, Ghulam; Pusparini , Denisa (Jurnal Kesehatan, 2022)
During their education, students are required to carry out various lecture processes and tasks, and also to complete academic assignments. The lots of lecture assignments that must be completed on time, and also a poor self-management of some students can cause academic stress. Self-efficacy and Emotional intelligence are possible factors that can reduce academic stress in students. This study aimed to determine the correlation between self-efficacy and emotional intelligence on student academic stress. Quantitative research method with a cross sectional approach was used to achieve the aim of the study. The population of this study was undergraduate nursing students of STIKes Sukabumi with a sample of 197 people, using stratified random sampling techniques. The instruments used in this study are self-efficacy variables using the Development of a College Academic Self-Efficacy, Emotional intelligence using the Emotional intelligence Self-Assessment Tool and academic stress using the Perception of Academic Stress scale (PASS). The data then analyzed using simple linear regression and multiple linear regression. The results of the study showed that the factors correlate to academic stress are self-efficacy variables (p 0.000; b -0.385; R2 0.883) and Emotional intelligence variables (p 0.000; b -0.862; R2 0.893). Self-efficacy and Emotional intelligence simultaneously have a negative relationship to academic stress (p 0.000; R2 0.899 with the equation Y=105.694+(-0.148X1)+(-0.540X2)+ε). In conclusion, there is a significant relationship between self-efficacy and emotional intelligence with academic stress of undergraduate nursing students.